Questioning the Universality of Storybook Reading: Examining Diversity in Family Literacy Practices - Laura Teichert; Tess Prendergast (Canadian Society for Studies in Education, 2014)
The purpose of this paper is to present a critical review of the literature documenting literacy related practices other than childhood storybook reading. The data sources were key studies of young children's literacy practices within the contexts of home and community. A critique of the ongoing privileging of storybook reading over other literacy practices as the most important component in children's literacy development is presented. Although storybooks are part of an overall literacy-rich environment, they are but one piece of a much larger puzzle that includes home literacy practices as well as scool literacy practices. In today's world, there is a need to re-evaluate this privileging in the course of becoming a reader.